KOMPARASI HAK ASUH DAN HAK NAFKAH ANAK DALAM PUTUSAN- PUTUSAN PERCERAIAN DI PENGADILAN NEGERI DAN PENGADILAN AGAMA KOTA SURAKARTA - Nugraheni, Anjar Sri Ciptorukmi; Cahyaningsih, Diana Tantri; Luthfiyah, Zeni (Yustisia, 2013)
AbstractThe high number of divorce in every year creates concern toward the children’s rights whose have parents divorce. Therefore, the writers did the research in order to identify the legal protection of children’s rights post parents divorce either for rights to rearing and rights to basic necessities. The research is involved into sociological research. The primary data was obtained through interview and the secondary data was coming from literature study from judge’s verdict in District court of Surakarta (either for general District court or religion District court). Technical analysis uses qualitative data specially using deductive method. This research shows that most of all the verdicts (judge’s decision), more than 75%, does not have any substantial decision regarding rights to rearing and rights to basic necessities (in both district court-general District court and religion District court). Based on this result, it means that the legal protection for the children’s who experience parents divorce is at very minimum legal protection for their rights.  The differences of legal protection, research by the writers between both district court, are in religion District court, the underwriter for rearing is given to the mother if the children are below 12 years old (mumayiz) and beyond 12 years old, the children could choose the underwriter is (until he or she is in the mature age-21 years old). Meanwhile, in general District court, there are no clauses regarding what and who are the underwriter, there is no mumayiz term including the differences uses of mature age between 18 years old or 21 years old.Keywords: divorce, rights to rearing, rights to basic necessities, age limit.AbstrakSemakin tingginya angka perceraian setiap tahunmemunculkan keprihatinan penulis tentang nasib anak- anak yang orangtuanya mengalami perceraian.Oleh karena itu penulis melakukan penelitian dengan tujuanmengidentifikasi perlindungan hukum terhadap hak-hak anak pasca perceraian kedua orangtuanya baik hak asuh maupun hak nafkah anak. Penelitian ini termasuk penelitian sosiologis.Data primer diperoleh melalui wawancara dan data sekunder diperoleh melalui studi pustaka putusan-putusan hakim di PN dan PA Kota Surakarta.Teknik analisis menggunakan analisis data kualitatif khususnya dengan metode deduktif. Hasil penelitian menunjukkan sebagian besar putusan (+75%) tidak mengandung amar putusan tentang hak asuh dan hak nafkah anak baik putusan perceraian di PN maupun PA.Hal ini berarti masih kurangnya perlindungan hokum terhadap hak-hak anak pasca perceraian kedua orangtuanya.Perbedaan perlindungan hukum yang diidentifikasi penulisantara di PA dan PN ialah jika di PA, kuasa hak asuh diseyogyakan adalah ibu jika anak belum berumur 12 tahun (mumayiz) dan setelah berumur lebih dari 12 tahun, anak dapat memilih siapa yang memegang hak asuh atas dirinya serta umur kedewasaan adalah 21 tahun. Sementara di PN, tidak ada ketentuan yang jelas siapa kuasa hak asuh, tidak dikenal istilah mumayyiz dan umur kedewasaan ada yang menganggap sampai berumur 18 tahun tapi ada juga yang sampai berumur 21 tahun .Kata kunci: Perceraian, hak asuh anak, hak nafkah anak, batas umur.